Advances in Stable Isotope Tracer Methodology Part 1: Hepatic Metabolism via Isotopomer Analysis and Postprandial Lipolysis Modeling. (January 2020) - Diniz Behn, Cecilia; Jin, Eunsook S; Bubar, Kate; Malloy, Craig; Parks, Elizabeth J; Cree-Green, Melanie
Stable isotope tracers have been used to gain an understanding of integrative animal and human physiology. More commonly studied organ systems include hepatic glucose metabolism, lipolysis from adipose tissue, and whole body protein metabolism. Recent improvements in isotope methodology have included the use of novel physiologic methods/models and mathematical modeling of data during different physiologic states. Here we review some of the latest advancements in this field and highlight future research needs. First we discuss the use of an oral [U- 13 C3 ]-glycerol tracer to determine the relative contribution of glycerol carbons to hepatic glucose production after first cycling through the tricarboxylic acid cycle, entry of glycerol into the pentose phosphate pathway or direct conversion of glycerol into the glucose. Second, we describe an adaptation of the established oral minimal model used to define postprandial glucose dynamics to include glycerol dynamics in an oral glucose tolerance test with a [ 2 H5 ]-glycerol tracer to determine dynamic changes in lipolysis. Simulation results were optimized when parameters describing glycerol flux were determined with a hybrid approach using both tracer-based calculations and constrained parameter optimization. Both of these methodologies can be used to expand our knowledge of not only human physiology, but also the effects of various nutritional strategies and medications on metabolism.